BMP, MEK, and WNT inhibition with NGN2 expression for rapid generation of hiPSC-derived neurons amenable to regional patterning: resource - Habich, Carina; Kowalski, Alexandra; Wachter, Astrid; Heimann, Michaela J.; Wolf, Michael; Kummer, Markus P.; Nicolaisen, Nathalie; Sliwinski, Christopher; Reinhardt, Lydia; Heil, Veronika; Lange, Timo; Untucht, Christopher; et al. (Stem cell reports, 2025)
Human induced pluripotent stem cells (hiPSCs) are a promising tool for studying neurological diseases and developing therapies for neurodegenerative diseases. Differentiation of hiPSCs into neurons can be achieved by dual SMAD inhibition (dSMADi) or by induced neurogenin 2 (NGN2) overexpression (“iNGN2”). Starting directly from hiPSCs, iNGN2 shortens the time to a neuronal stage but leads to neurons partially resembling peripheral or posterior fates while dSMADi more faithfully recapitulates telencephalic development. To modify the iNGN2 approach, we applied an accelerated induction paradigm that is dependent on the inhibition of BMP, MEK, and WNT pathways (“BMWi”), to commit hiPSCs into a telencephalic fate before iNGN2. The resulting neurons showed strong expression of telencephalic markers, with decreased levels of peripheral and posterior marker genes compared to iNGN2 alone. The resulting telencephalic neurons are suitable for a tau aggregation assay. Furthermore, we could demonstrate that during BMWi treatment, the cells are amenable to additional regional patterning cues. This allowed the generation of neurons from different regions of the CNS and peripheral nervous system (PNS), which will significantly facilitate in vitro modeling of a range of neurodevelopmental and neurodegenerative disorders.
Online verfügbar: 19. Juni 2025, Artikelversion: 8. Juli 2025
Gesehen am 04.09.2025